Assessing the Prevalence of Ectopic Cerebellar Tonsils and Accompanying Symptoms in Individuals with Various Headaches - Ghodsiyeh Azarkar; Sahar Nemati; Shabnam Vafadar; Gholam Reza Sharifzade; Arash Ziaee; Hossein Ashrafi (Journal of the Belgian Society of Radiology, 2023)
Objectives: Chiari malformation exhibits well-defined clinical signs, symptoms, and incidence rates in clinical studies. However, cerebellar tonsil ectopia presents with ambiguous symptoms and undetermined incidence rates in numerous studies. Our objective was to determine the incidence of cerebellar tonsil ectopia in individuals with headaches and identify additional clinical symptoms. This aims to improve diagnosis accuracy for clinicians and neurologists, leading to more effective treatment approaches. Methods: A cross-sectional study conducted in 2022 included 2305 participants aged 4–78 years presenting with headache. Chiari malformation was diagnosed using magnetic resonance imaging (MRI) scans, with a definition of cerebellar tonsil herniation extending beyond 5mm into the cervical canal. Results: The prevalence of Chiari malformation was 3.4%, with no significant gender difference (p = 0.72). There was a significant correlation between Chiari malformation and headache exacerbation due to the Valsalva maneuver (p < 0.001) and the presence of vertigo (p < 0.001). No significant association was found between Chiari malformation and accompanying symptoms such as nausea (p = 0.43), photophobia (p = 0.2), phonophobia (p = 0.52), and speech disorders (p = 0.45). Conclusion: These findings suggest a notable prevalence of Chiari malformation among headache patients and its association with specific headache characteristics, such as acute and occipital headaches, exacerbation by the Valsalva maneuver, and the co-occurrence of vertigo. These results underscore the need to consider Chiari malformation in the differential diagnosis of patients presenting with these specific headache features.